Roles of p38-MAPK in insulin resistant heart: Evidence from bench to future bedside application - Sarawut Kumphune (2018)
Insulin resistance is associated with the impairment of the response of insulin receptor to insulin, resulting in the reduction of glucose uptake, leading to the alteration of myocardial glucose metabolism, impairment of cardiac electrophysiology, and increased susceptibility to ischemia-induced myocardial injury. Insulin resistance is associated with the impairment of the intracellular insulin signal transduction pathway. Among the MAPK family, p38-MAPK is a serine/threonine protein kinase, which has been shown to play an important role in cellular responses to various kinds of stress, including insulin resistance. Since growing evidence indicates the involvement of p38-MAPK in cardiovascular dysfunction, it is possible that the activation of p38-MAPK is responsible in part as a causative mechanism for cardiovascular complications in the insulin resistant heart. In addition, several anti-diabetic drugs have been shown to affect the myocardial p38-MAPK pathway. The effect of these drugs on p38-MAPK could be associated with their cardiovascular results in patients with insulin resistance. In this article, the signal transduction pathways of myocardial p38-MAPK activation in the insulin resistant heart, as well as the effects of anti-diabetic drugs on the myocardial p38-MAPK pathway, are comprehensively reviewed. Furthermore, the possible therapeutic approach regarding the utilization of a p38-MAPK inhibitor in diabetes patients to prevent cardiovascular complications is also addressed. © 2013 Bentham Science Publishers.